Analysis of Lead Chromate, Insect Infestation, Urea and pH in Various Brands of Instant Noodles Marketed in Malaysia - ATM Emdadul Haque; Jannathul Firdous; Amirul Ashraf Mohd Hamdi; Intan Nurliyana Ahmad Shafri; Najiha Arissa Norhisham; Nur Amirah Balqis Mohd Salleh; Nur Iffah Ab Rani; Rafiqah Farhanah Redzuan (Asian Journal of Medicine & Health Sciences, 2022)
Aim: Instant noodles have been a famous choice for people of all ages. However, there are more chemicals and harmful contents that have been used in the food production process which people are not aware of and not having concern about the negative effects on the human’s health. Lead chromate, urea and insect infestation have been reported to cause significant health problem to human being. Moreover, deviation of normal pH can lead to metabolic disturbances. Methods: In this study, qualitative analysis of some additive chemicals such as urea, lead chromate, insect infestation and pH determination were done. Results: Among the 6 brands tested based on local-made product brands, we found that 2 of the brands contained lead chromate. As for insect infestation and urea test, negative results were observed and recorded for all instant noodles brands. For the pH value, one of the brands were found most alkaline and one as the most acidic. Conclusion: Among the six instant noodles brands, two brands of instant noodles contained lead chromate and one was the most alkaline while the other with the most acidic content